Comprehensive Study of Digital Transformation in General Healthcare Delivery and Addressing Disparities across Diverse Populations - Alahmadi, Abdullah Hussain Ateeq Allah; Ali, Nusaibah Mahmoud; Almutairi, Amer; Shuwayhi, Hanan Abdu; Alharbi, Meznah Hamad Nafl; Alamri, Hend Aiadh; Alharbi, Majed Hameed; Altarjami, Nahlah Aied Abed (Journal of Ecohumanism, 2024)
Healthcare technology is the key driver within the current society, hence contributing to the achievement of the set goals regarding the delivery of healthcare services. The World healthcare system is slowly incorporating digital technology such as telemedicine, artificial intelligence, electronic health records and Mobile health applications. However, as with digital solutions to healthcare systems, the tremendous potential for presenting improved services comes with corollary issues regarding equity, access, and health disparities. Thus, this research investigates how DT has shaped general healthcare delivery solutions, emphasizing the effects on disparate populations. Reading the available literature and the available case and quantitative data on the impact of digital healthcare solutions, this research describes and evaluates the role of digital solutions in tackling healthcare disparities. Moreover, it also identifies ways to address the challenges to equitable and efficient healthcare delivery through technology.